Circadian-related heteromerization of adrenergic and dopamine D₄ receptors modulates melatonin synthesis and release in the pineal gland. - Sergio González; David Moreno-Delgado; Estefanía Moreno; Kamil Pérez-Capote; Rafael Franco; Josefa Mallol; Antoni Cortés; Vicent Casadó; Carme Lluís; Jordi Ortiz; Sergi Ferré; Enric Canela; et al. (PLoS Biology, 2012)
The role of the pineal gland is to translate the rhythmic cycles of night and day encoded by the retina into hormonal signals that are transmitted to the rest of the neuronal system in the form of serotonin and melatonin synthesis and release. Here we describe that the production of both melatonin and serotonin by the pineal gland is regulated by a circadian-related heteromerization of adrenergic and dopamine D₄ receptors. Through α(₁B)-D₄ and β₁-D₄ receptor heteromers dopamine inhibits adrenergic receptor signaling and blocks the synthesis of melatonin induced by adrenergic receptor ligands. This inhibition was not observed at hours of the day when D₄ was not expressed. These data provide a new perspective on dopamine function and constitute the first example of a circadian-controlled receptor heteromer. The unanticipated heteromerization between adrenergic and dopamine D₄ receptors provides a feedback mechanism for the neuronal hormone system in the form of dopamine to control circadian inputs.